Assessing prospective memory in children using the Memory for Intentions Screening Test for Youth (MISTY). Issue 3 (20th March 2021) - Mills, Ginger N.; Garbarino, Julianne T.; Raskin, Sarah A.
Abstract: Objective: Prospective memory (PM) is defined as the ability to remember to complete an intention in the future. The first aim of this study was to address the need for clinically useful measures of PM in children, by assessing the psychometric properties of a new measure of PM in children and adolescents, the Memory for Intentions Screening Test for Youth (MISTY). The second aim was to assess the relationship between prospective memory and age, particularly the relationships between age and the impact of different PM task demands. The third aim was to examine children's performance on different aspects of PM, such as time-based versus event-based cues. Method: One-hundred twenty-four children between the ages of 4 and 15 were given the MISTY. Results: Analyses revealed good internal consistency among the eight individual MISTY trials and among the six MISTY subscales which included two different cue types (event-based and time-based), two different time delays (2 minutes and 10 minutes), and two different response types (action and verbal). Results also revealed good split-half and inter-rater reliability. Findings highlighted significant correlations between age and the MISTY total score and all subscales, consistent with PM lifespan research. On the MISTY, children overall performed better on event-based cues than on time-based cues, and on shorter time delays than longer ones; there was no effect of response type (i.e. action vs. verbal response). Conclusions: The MISTY is a promising instrument with sound psychometric properties that could be useful in both clinical and research settings. Additionally, this study highlights the age-related process of PM development in children.